DEVELOPMENT OF CYCLIC INJECTION SCHEMES IN HYDRAULIC FRACTURING - Mohammad Hossein Arabnejad; Morteza Ahmadi (Rudarsko-geološko-naftni Zbornik)
Due to the increasing use of hydraulic fracturing in the exploitation of geothermal energy and the increase in the extraction of hydrocarbon resources, the depth and scale of this operation has expanded, which has led to the creation of special requirements and challenges. One of the most important challenges is the creation of earthquakes caused by the triggering of faults in the region. In order to solve this problem, various studies are being done. In the current study, based on the aforementioned points, three proposed methods of cyclic injection under the triaxial stress regime have been investigated and assessed to simulate the operation as accurately as possible. Stepwise injection (SI), stepwise cyclic injection (SCI) and stepwise progressive cyclic injection (SPCI) are three proposed methods that the results of the breakdown pressure, as well as the different parameters of acoustic emission events have been studied. The experiments were carried out by a laboratory true triaxial loading device. The results confirm the reduction of the breakdown pressure level in all three proposed methods. Stepwise injection has the highest reduction in fracture pressure compared to the test time. The results of the stepwise cyclic injection method show a decrease in the amount of energy released during the failure, so it can be considered in reducing the risk of earthquakes. Due to the combined effect of reducing the breakdown pressure level and creating a wider fracture network, the stepwise progressive cyclic injection method possibly has a better efficiency in the application of geothermal resource exploitation.